The evolution of the economic dimension of agricultural farmings in Romania - Gabriela-Dalila Stoica; Eduard Alexandru Dumitru (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
This paper presents a general analysis of agricultural holdings in Romania. Thus, in this study, the economic size of the agricultural holding, the used agricultural area, the total crop production and the gross income of the farms were analyzed, depending on the size of the agricultural holdings expressed in standard output. In addition, to clearly highlight the existing situation, statistical indicators such as standard deviation, coefficient of variation and growth rate were calculated. The current disparities are significant, and there is no clear evidence that they will be reduced or eliminated, because the structural problems facing Romanian agriculture can only be debated over a long period of time. The data used were extracted from the Agricultural Accounting Information Network (RICA), for the period 2007-2021. The obtained results support the fact that the average economic size at the level of agricultural holdings in Romania is relatively stable, as far as this indicator is concerned. At the same time, the agricultural areas used decrease and the total productions of the crops increase for all types of economic sizes, except for holdings between 8 000 and 25 000 euros.
Keywords: Q10; 330; Agricultural holdings; economic dimension; Romania